2018
DOI: 10.1080/10790268.2018.1544879
|View full text |Cite
|
Sign up to set email alerts
|

Bone changes in the lower limbs from participation in an FES rowing exercise program implemented within two years after traumatic spinal cord injury

Abstract: Objective: To determine the effect of a functional electrical stimulation (FES) rowing program on bone mineral density (BMD) when implemented within two years after SCI. Design: Prospective. Setting: Health Care Facility. Participants: Convenience sample; four adults with recent (<2 years) traumatic, motor complete SCI (C7-T12 AIS A-B). Intervention: A 90-session FES rowing exercise program; participants attended 30-minute FES training sessions approximately three times each week for the duration of their part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Notwithstanding these differences, we do not see any reason to discredit the validity of our results. It should be noted we use our results to propose a collective reflection on which leg muscles to stimulate in FES-Rowing applications, hoping to optimise the health benefits of FES Rowing [3,6] and to increase its feasibility and therefore, its popularity among SCI individuals. Given our common experience that motor proficiency arises with the suppression of unnecessary muscle activity (i.e., cocontraction), shaping the stimulation of leg muscles according to the excitation of leg muscles observed for elite than novice rowers is more likely to delay fatigue development and to produce smooth kinematic profiles [16,44].…”
Section: A Few Considerations On the Validity Of Current Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding these differences, we do not see any reason to discredit the validity of our results. It should be noted we use our results to propose a collective reflection on which leg muscles to stimulate in FES-Rowing applications, hoping to optimise the health benefits of FES Rowing [3,6] and to increase its feasibility and therefore, its popularity among SCI individuals. Given our common experience that motor proficiency arises with the suppression of unnecessary muscle activity (i.e., cocontraction), shaping the stimulation of leg muscles according to the excitation of leg muscles observed for elite than novice rowers is more likely to delay fatigue development and to produce smooth kinematic profiles [16,44].…”
Section: A Few Considerations On the Validity Of Current Resultsmentioning
confidence: 99%
“…However, given that the total number of stimulation channels is often limited to four-six, distributed between muscles in both legs, our results ( Figure 3) suggest recovery could be more easily facilitated by stimulation of tibialis anterior than hamstrings. During the rowing drive phase, the decision of which muscles to stimulate is less discussable; according to previous and current results, quadriceps would seem to be the main knee extensor muscles (current results; see also [1][2][3][4][5][6]). It should be noted though that soleus was consistently activated during the drive phase, both across subjects and legs (Figures 2-4).…”
Section: Identification Of Key Leg Muscles To Target In Fes-rowing Apmentioning
confidence: 87%
See 1 more Smart Citation
“…The use of active orthoses in combination with FES is an effective strategy to optimize the outcomes of gait rehabilitation training. Using hybrid orthosis to stimulate the lower extremity muscles has proven to evoke muscle hypertrophy, increase strength, improve cardiopulmonary fitness, and reduce fatigue during gait, even in subjects with severe spasticity (Nightingale et al, 2007; Qiu and Taylor, 2016; Deley et al, 2017; Ekelem and Goldfarb, 2018; Lambach et al, 2018). Complete recent reviews of hybrid exoskeletons can be found in Stewart et al (2017) for the upper limbs, and Anaya et al (2018) for the lower limbs.…”
Section: Introductionmentioning
confidence: 99%
“…Using evidence from experimental results and biomechanical data 15 Lambach et al . produce an empirical measure that connects changes in BMD in people with SCI with the magnitude and frequency of bone loading forces 16 .…”
Section: Introductionmentioning
confidence: 99%